Effect of MoS2 Yolk-Shell Nanostructure on the Thiophene Separation Performance of PEG Membrane - Ziman Hou; Ping Peng; Yongqiang Lan; Zihui Wu; Jianhua Wang (Advances in Polymer Technology)
Constructing facilitated transport based on π-complexation has been drawing more and more attention in mixed matrix membranes (MMMs) for pervaporative desulfurization. Herein, a unique molybdenum disulfide (MoS2) yolk-shell nanostructure (MYNS) was prepared and incorporated into the polyethylene glycol (PEG) matrix to fabricate MMMs for model gasoline desulfurization by PV. Moreover, the effects of MYNS content, feed sulfur concentration, and feed temperature on the performance of PEG/MYNS MMMs were evaluated. It was found that there is good interfacial compatibility between the MYNS filler and the PEG matrix, and the resultant MMMs show enhanced swelling resistance against thiophene. The PV results revealed that the as-fabricated MMMs are thiophene-selective, and their desulfurization performance in the pervaporative removal of thiophene from n-octane is remarkably evaluated due to the addition of MYNS. The MMMs display the highest sulfur enrichment factor of 4.02 with an associated permeation flux of 2587 g·m−2·h−1 with the MYNS loading of 3 wt. % when carrying out in an n-octane and thiophene (500 μg·g−1) mixture at 343 K. Furthermore, a consistent increment in the permeation flux accompanied with a continuous reduction in the enrichment factor was observed with increasing the feed sulfur concentration and feed temperature. This work may offer great potential for practical gasoline desulfurization applications.